Ilmu Pengetahuan dan Teknologi dalam Perilaku Bullying: Studi Kasus Siswa di Grup WhatsApp SMP Swasta Al Ma'sum Kabupaten Langkat - Syahdina Ahbal; Susi Fitria Dewi; Al Rafni; Fatmariza (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to explore the role of science and technology in bullying behavior that occurs through WhatsApp groups among students of Al Ma'sum Private Junior High School, Langkat Regency. The method used was a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. The results showed that common forms of bullying include verbal bullying, cyberbullying, and social exclusion, which are triggered by factors such as lack of empathy, peer pressure, and the influence of negative content on social media. This study recommends science-based prevention strategies, including anti-bullying education, awareness campaigns, and active parental involvement, to reduce bullying behavior in school settings. The findings provide important insights into the dynamics of bullying in the digital age and emphasize the need for a more systematic approach to tackling it.